To solve the equation \( u + \frac{11}{3} = \frac{1}{3} \) using inverse operations, we need to isolate \( u \).
- Subtract \( \frac{11}{3} \) from both sides of the equation:
\[ u + \frac{11}{3} - \frac{11}{3} = \frac{1}{3} - \frac{11}{3} \]
This simplifies to:
\[ u = \frac{1}{3} - \frac{11}{3} \]
- Now, calculate the right side:
\[ \frac{1 - 11}{3} = \frac{-10}{3} \]
Thus, we have:
\[ u = -\frac{10}{3} \]
Now, let's look at the provided answer options:
A: \( 4 \)
B: \( 103\frac{10}{3} \)
C: \( -4 \)
D: \( -103-\frac{10}{3} \)
None of the options are correct because the solution is \( u = -\frac{10}{3} \). If you are expected to find a number that matches exactly with the answer choices, please confirm the provided options or explain any additional context.